456. THE PROGNOSTIC IMPACT OF TUMOR BUDDING IN ESOPHAGEAL ADENOCARCINOMA. (24th September 2022) - Fiocca, Roberto; Mastracci, Luca; Lugaresi, Marialuisa; Grillo, Federica; D'Errico, Antonietta; Malvi, Deborah; Spaggiari, Paola; Tomezzoli, Anna; Albarello, Luca; Ristimäki, Ari; Bottiglieri, Luca; Bonora, Elena; et al.
Abstract: In a previous study on esophageal adenocarcinoma (EAC) cases submitted to surgery (without neoadjuvant treatment), an algorithm (EACGSE classification) 1 based on morphologic distinctions provided significant prognostic impact. Tumor budding is a specific type of invasive growth pattern and was found to be an important prognostic parameter in gastrointestinal cancers. 2–3 We aimed to evaluate the prevalence of budding in glandular adenocarcinomas and its impact on survival. The EAC cohort classified according to EACGSE 1 was included in the study: among the different histotypes, 215 cases, classified as well (WD) and poorly (PD) differentiated glandular adenocarcinomas, were considered. Tumor budding was defined as single cells or clusters of up to four cells at the invasive margin. Budding was grouped according to ITBCC 2 into Bd1 (0-4 buds), Bd2 (5-9 buds), and Bd3 (10 or more buds). Furthermore, the most prognostically relevant cut off for bud number in EAC was defined by ROC analysis. Cancer specific survival analyses were performed using the Kaplan–Meier method and Cox regression analyses. Tumor budding was assessed in one hotspot (a field measuring 0.785 mm2) at the invasive front and ROC analysis identified 8 buds per field cut off as the most informative in relation to survival. By using this cut off, frequency of budding was higher in glandular PD (84/124, 68%) cases than in WD ones (7/91, 8%, p < 0.001). Budding was a strong negative predictor of survival both in univariate (p < 0.001) and multivariate analyses (p < 0.001) (Fig. 1). Using the 3 categories proposed by ITBCC, 2 budding was significantly related to survival in univariate analysis (p = 0.006) but lost significance in multivariate analysis. Tumor budding showed a prognostically negative impact in glandular EACs. The 8 buds per field cut off appears to provide the best prognostic discriminant. Tumor budding assessment should be added to the identification of other prognostic factors already described in the same series (stage, histotype and vascular invasion). 1